Elucidating the Neuropathologic Mechanisms of SARS-CoV-2 Infection - Pacheco-Herrero, Mar; Soto-Rojas, Luis O.; Harrington, Charles R.; Flores-Martinez, Yazmin M.; Villegas-Rojas, Marcos M.; León-Aguilar, Alfredo M.; Martínez-Gómez, Paola A.; Campa-Córdoba, B. Berenice; Apátiga-Pérez, Ricardo; Corniel-Taveras, Carolin N.; Dominguez-García, Jesabelle de J.; Blanco-Alvarez, Víctor Manuel; et al. (Frontiers in Neurology, 2021)
The current pandemic caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a public health emergency. To date, coronavirus disease 2019 (COVID-19) has caused about 99.3 million accumulated cases and 2.13 million deaths worldwide. Previous pieces of evidence suggest that SARS-CoV-2 may affect the central nervous system (CNS) and cause neurological symptoms in COVID-19 patients. It is also known that angiotensin-converting enzyme-2 (ACE2), the primary receptor for SARS-CoV-2 infection, is expressed in different brain areas and cell types. Thus, it is hypothesized that infection by this virus could generate or exacerbate neuropathological alterations. However, the molecular mechanisms that link COVID-19 disease and nerve damage are unclear. In this review, we describe the routes of SARS-CoV-2 invasion into the central nervous system. We also analyze the neuropathologic mechanisms underlying this viral infection, and their potential relationship with the neurological manifestations described in patients with COVID19, and the appearance or exacerbation of some neurodegenerative diseases.